Christian Literature in Chinese Contexts - Lai, John T. P. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Christianity in China has a history dating back to the Tang Dynasty (618-907 CE), when Allopen-the first Nestorian missionary-arrived there in 635. In the late sixteenth century, Matteo Ricci together with other Jesuit missionaries commenced the Catholic missions to China. Protestant Christianity in China began with Robert Morrison, of London Missionary Society, who first set foot in Canton in 1807. Over the centuries, the Western missionaries and Chinese believers were engaged in the enterprise of the translation, publication, and distribution of a large corpus of Christian literature in Chinese. While the extensive distribution of Chinese publications facilitated the propagation of Christianity, the Christian messages have been subtly re-presented, re-appropriated, and transformed by these works of Chinese Christian literature. This Special Issue entitled "Christian Literature in Chinese Contexts" examines the multifarious dimensions of the production, translation, circulation, and reception of Christian literature (with "Christian" and "literature" in their broadest sense) against the cultural and sociopolitical contexts from the Tang period to modern China. The eight articles in this volume cover a variety of intriguing topics, including the literary/translation endeavors of Western missionaries in Chinese, the indigenous works of the Chinese Christians, the interaction between the Christian and Chinese literary traditions, Chinese reception of the Bible, and numerous other relevant concepts.